Industrial mobillization the relevant histrory - Vawter, Roderick L. (Mobilization and defense management studies, 1983)
The basic premise of this historical study is that industrial mobilization lessons of the past provide answers for many of today's problems. The author contends that current industrial mobilization planners should draw lesseons more from the Korean War effort than from World War II.